The Costs of Missing the Millennium Development Goal on Gender Equity - Dina Abu-Ghaida; Stephan Klasen (Institute for the Study of Labor (IZA), 2004)
At the Millennium Summit, the world community pledged to promote gender equality and chose as a specific target the achievement of gender equity in primary and secondary education by the year 2005 in every country of the world. Based on the findings from a growing empirical literature that suggests that gender equity in education promotes economic growth and reduce fertility, child mortality, and undernutrition, we estimate what the costs in terms of growth, and forgone fertility, mortality and undernutrition reduction, will be for the 45 countries that are, on current projections, unlikely to meet the target. Our estimates suggest that, by 2005, the countries that are off track are likely to suffer 0.1-0.3 percentage points lower per capita growth rates as a result and will have 0.1-0.4 more children per woman, and, by 2015, an average of 15 per 1000 higher rates of under five mortality and 2.5 percentage points higher prevalence of underweight children under five. Sensitivity analyses suggest that the results are quite robust to using different specifications and approaches to estimating these losses.
Keywords: I2; J16; J13; J7; 330; gender bias; education; millennium development goals; growth; Bildungschancen; Gleichberechtigung; Frauenbildung; Soziale Kosten; Schätzung; Welt